2009
DOI: 10.1097/mpg.0b013e31817efbf7
|View full text |Cite
|
Sign up to set email alerts
|

Bowel Habits and Toilet Training in a Diverse Population of Children

Abstract: Most of the children between 5 and 8 years of age have a medium-size bowel movement daily or every other day without straining or withholding. Although African American children toilet train at an earlier age than do white children, bowel habits appear to be similar. A sizeable subgroup of children presenting to primary care providers have a history that is consistent with constipation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
49
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 27 publications
8
49
2
1
Order By: Relevance
“…Retentive behaviour was more common in boys (56.6%) which are similar to study by Wald et al, [12]. In our study faecal soiling was present in 40.4% of children and was equally distributed between both sexes.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Retentive behaviour was more common in boys (56.6%) which are similar to study by Wald et al, [12]. In our study faecal soiling was present in 40.4% of children and was equally distributed between both sexes.…”
Section: Resultssupporting
confidence: 80%
“…Faecal soiling was 30.8% in the study conducted by Khanna et al, [1]. In the study by Wald et al, faecal soiling was more common in boys [12]. Faecal soiling was observed in 84% of children at presentation by Voskuijl which was very high as compared to our study [13].…”
Section: Resultscontrasting
confidence: 42%
See 1 more Smart Citation
“…Most studies demonstrate that daytime UI is more common in girls, 9 although the difference may be slight. The ages at which diapers for urine were discontinued are in keeping with the literature on toilet training in children, where there is general agreement that girls master toilet training earlier than boys, 25 and that daytime bladder control precedes nighttime control. 26 Some type of minor daytime UI was reported by approximately a fourth of the study population.…”
Section: Discussionmentioning
confidence: 85%
“…Wald et al found retentive behavior to be more common in boys similar to ours. 17 In this study, fecal soiling was present in 44.05% of children with slight female preponderance (n=48). Fecal soiling was 30.8% in the study conducted by Khanna et al In the study by Wald et al; fecal soiling was more common in boys.…”
Section: Discussionmentioning
confidence: 99%